1996
DOI: 10.1007/bf00182496
|View full text |Cite
|
Sign up to set email alerts
|

Double congenital patella: case report and review of the literature

Abstract: The authors report a case of double congenital patella, which is a rare finding. This anomaly was studied using radiography, CT and MR. Magnetic resonance imaging has enabled us to make an accurate anatomical evaluation of the double congenital patella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…En orden descendente de frecuencia encontramos variaciones en su osificación (patela bipartita, tripartita), forma, posición e hipoplasia. Sin embargo la duplicación de la patela es extremadamente rara y se considera una malformación congénita 1 , aunque en algunos casos se proponen anomalías del desarrollo influenciadas por elementos externos 3 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En orden descendente de frecuencia encontramos variaciones en su osificación (patela bipartita, tripartita), forma, posición e hipoplasia. Sin embargo la duplicación de la patela es extremadamente rara y se considera una malformación congénita 1 , aunque en algunos casos se proponen anomalías del desarrollo influenciadas por elementos externos 3 .…”
Section: Discussionunclassified
“…La duplicación horizontal se describió por primera vez en 1902 y posteriormente en 1925 5,6 , apareciendo más tarde una serie de casos en la literatura, siendo la más frecuente de todas las duplicaciones 1 . Existen algunos casos de patologías adquiridas que simulan este tipo de duplicación patelar.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Congenital duplication of the patella is called double patella [1]. To our knowledge, double patella is extremely rare, and the total number of reported cases is only 15.…”
Section: Discussionmentioning
confidence: 99%
“…Double patella is a congenital malformation involving 2 independent cartilaginous centers that each give rise to a patella, complete with its own aponeurotic expansion and patella tendon [2]. MRI is very important to accurately evaluate the anatomical aspects and confirm the diagnosis of a double patella [1]. The available literature showed that in the majority of cases with double patella, the position of the second patella is superior or inferior compared with that of the normal patella, although the position of the second patella in relation to the first is unimportant.…”
Section: Discussionmentioning
confidence: 99%